1979
DOI: 10.1007/bf02408050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of magnesium depletion on matrix-induced endochondral bone formation

Abstract: The effect of magnesium deficiency on bone cell differentiation and bone formation was investigated using in vivo matrix-induced endochondral ossification as a test system. Demineralized bone matrix was implanted subcutaneously in young (35-day-old) male Long-Evans rats that had been fed a semisynthetic Mg-deficient diet (50 ppm Mg) for 7 days. Plasma Mg levels were reduced to 25-30% of control values at that time. Control rats were paired the same diet, supplemented to contain 1000 ppm Mg. The implants were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Mg deficiency has also been observed to delay the onset of mineralization of newly formed cartilage matrix and bones [77]. Whether this is due to the effect on crystal formation or to some other process in mineralization is unclear.…”
Section: Abnormal Bone Crystal Formation and Mineralizationmentioning
confidence: 98%
“…Mg deficiency has also been observed to delay the onset of mineralization of newly formed cartilage matrix and bones [77]. Whether this is due to the effect on crystal formation or to some other process in mineralization is unclear.…”
Section: Abnormal Bone Crystal Formation and Mineralizationmentioning
confidence: 98%
“…Research concerning the effects of a low Mg supply on calcium (Ca) mobilisation of cows has shown that hypomagnesaemic cows had lower Ca mobilisation rates in response to hypocalcaemia induced by the intravenous infusion of disodium ethylenediaminetetra-acetate (Na2EDTA) than normomagnesaemic cows (4,7,30). In studies with rats it was found that the rates of bone mineralisation (12,32), bone formation (12) and bone resorption (12) in Mg-deficient rats were lower than in rats which had been fed adequate Mg. Histological examination of bones from Mg-deficient dogs showed a picture compatible with skeletal inactivity (8). These observations indicate that in Mgdeficient animals the rate of bone turnover is decreased.…”
Section: Introductionmentioning
confidence: 99%
“…It plays essential roles in metabolic pathways as an enzyme catalyst [16,17], in cell structure and function [18,19], and in bone formation and growth by promoting calcium deposition [20,21]. Although Mg is a highly electrochemically active anodic metal [13], advances in metallurgical alloy processing via phase design [13,22] and heat treatment [23] have opened avenues to address the rapid corrosion of Mg in order to meet clinical requirements.…”
mentioning
confidence: 99%